Cryogenic adsorption pumps for REB accelerrators - Batrakov, A.B.; Kravchenko, V.A.; Lonin, Yu.F.; Chernyshenko, V.Ya. (Вопросы атомной науки и техники, 2004)
It is known that in relativistic electron bunching (REB) accelerators the main residual gases are air components.
Under irradiation in targets made of different materials being studied, a significant increase of a level of such gases
as hydrocarbons, aqueous vapor and hydrogen is observed. Therefore, it is clear that for improvement of vacuum
conditions for a REB accelerator it is necessary to apply pumps which should permit to realize a high rate of pumping out of main residual gases and those of them the level of which increases considerably in targets under irradiation. We propose to complete the available equipment for pumping of REB accelerators with cryogenic adsorption
pumps. They are to be placed in accelerators so that they can serve as additional means for protection of the target
chamber volume against hydrocarbon coming from the available pumping equipment. It will make it possible to improve significantly the initial vacuum conditions in the working volume, and, furthermore, to reduce the time between experimental pulses. Відомо, що в прискорювачах РЕП основними залишковими газами є гази повітря. При опромінюванні
досліджуємих мішеней із різноманітних матеріалів спостерігається значне підвищення рівню таких газів, як
вуглеводні, водяні пари і водень. Тому для поліпшення вакуумних умов прискорювачів РЕП необхідно
використання насосів, які би мали велику швидкість відкачки основних залишкових газів, і тих із них, рівень
яких суттєво зростає при опромінюванні мішеней. Нами пропонується доповнити існуючи засоби відкачки
прискорювачів РЕП кріогенними адсорбційними насосами, які розташовуються в прискорювачах таким
чином, щоби вони стали допоміжним засобом захисту об’єму від поступаючих вуглеводню та інших газів з
мішені. Це дозволить значно поліпшити початкові вакуумні умови і привести до суттєвого скорочення часу
між імпульсами. Известно, что в ускорителях РЭП основными остаточными газами являются компоненты воздуха. При
облучении исследуемых мишеней из различных материалов наблюдается значительное повышение уровня
таких газов, как углеводороды, водяные пары и водород. Поэтому очевидно, что для улучшения вакуумных
условий ускорителя РЭП необходимо применение насосов, которые бы позволяли реализовывать большую
быстроту откачки основных остаточных газов, так и тех из них, уровень которых существенно возрастает
при облучении мишеней. Нами предлагается дополнить наличные средства откачки ускорителей РЭП криогенными адсорбционными насосами, при этом размещать их в ускорителях так, чтобы они стали дополни-
тельным средством защиты объема камеры мишени от поступления углеводородов со стороны наличных
средств откачки. Это позволит значительно улучшить начальные вакуумные условия в рабочем объеме, а с
другой стороны, сократить время между экспериментальными импульсами.